If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -2x = 81 Combine like terms: x + -2x = -1x -1x = 81 Solving -1x = 81 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-1'. x = -81 Simplifying x = -81
| 6-3y-10y=-15 | | x^2+6x-8=72 | | 6-13y-10=-15 | | 0.3x+0.03x+0.003x+0.0003x+0.00003x=3 | | 4x+11+6x-1=180 | | y=2ln | | 2(x+6)=86 | | X^2+2x=104 | | x*x-14x+24=0 | | 3(4-6)+12(-4)+2= | | .6[n+10]=3.6 | | 5r-7=33 | | x^2-c=6 | | -x-4y=-11 | | 5-2(3-2)=4(6y-4)+8 | | x*x-14x+49=25 | | 3v-9=-9(v-7) | | 2z+11=5z-7 | | (-4x-3y-8)+(5y-2x+1)= | | x+-2x-1=-x-1 | | y=ln(x^2-3x+2) | | 8-(x+9)=x+4(3x-1) | | y=2x-6x+3 | | y=8x-22 | | (x-7)(x-7)=25 | | 4x-(3x+8)=6 | | 99=2(-7b-3)+7 | | 7.50+22.50x=142.50 | | 2x+8+3+4x=35 | | =9st(7s-6t^2) | | -4-73+5n=-14 | | 5+5*7=77 |